Aplicación de las imágenes Landsat TM al estudio de la isla térmica de Zaragoza. Primeros resultados - De La Riva, Juan Ramón; Cuadrat, José María; López Martín, Fernando; Martí, Alberto (Geographicalia, 2017)
A qualitative analysis of the thermic pattern caracteristics of Zaragoza is carried out by two Landsant Thematic Mapper images (10 h GTM), both in relation with its immediate environment and its internal changes.
Keywords: Thermic island; urban climate; Landsant TM; Zaragoza